A que(m) atendem as categorizações identitárias?: um estudo sobre o pensamento de vida LGBT+ - Silva, San Thiago de Araújo e (2022)
ABSTRACT The knowledge and discourses that circulate among the subjects enrolled in the LGBT+ life thinking, a counter-hegemonic discursive regime to the cisheteronormative colonialist framework, demand a self-analysis, since they reproduce oppressive patterns. Thus, my aim with this study is to investigate, on the one hand, the discursive functioning of the LGBT+ Movement, regarding the way identities are created from which individuals start to (self)represent themselves in society; and, on the other hand, to discursively identify the ways how LGBT+ subjects perceive the movement and signify its practices, knowledges, and discursivities. Therefore, I develop a discursive study, based on the theoretical conceptions of Michel Foucault and Michel Pêcheux, seeking to understand the conditions of possibility and the effects of meaning constructed in the enunciations of a) the LGBT+ Movement; and b) LGBT+ subjects. For that, I take all the slogans already used in the editions of the Uberlândia Pride Parade; and formulations in response to a questionnaire proposed to individuals who call themselves LGBT+ and who volunteered to participate in this research through its dissemination in LGBT+ Facebook groups. In this way, I identify three regimes of enunciability of the LGBT+ Movement: in the first, I organize slogans that function in order to politically and socially represent the subjects of the movement; in the second, I arrange the slogans that warn of prejudices experienced specifically by such subjects; and, in the third, I expose the slogans that are directed at celebrating the fact that these subjects are diverse from the norm. From the knowledge discursivized by the LGBT+ subjects who participated in the research, I identify colonialist meaning effects constituting power relations in the subjective interrelations of the identities represented by the movement; moreover, I perceive the enunciations of the research participants being made possible by the feeling of representative inequality/ insufficiency promoted by the movement to each identity category. From this, I reflect on the need for the LGBT+ Movement to perform a self-critique of the political strategies it assumes, questioning itself in the direction of analyzing which regimes of knowledge they have served and put into circulation. Finally, I consider the importance that identity agendas have had, to some extent, to the LGBT+ Movement, but in contrast, by analyzing the colonialist traversals and oppressive effects that displace within LGBT+ life thinking, I ponder the possibility that the movement, by positioning itself in a queer and decolonializing way, can overcome the classificatory functioning, disrupting it.